Dampak penggunaan media sosial pada mental health remaja: A systematic literature review - Salsabila, Salma Nehaya (Maliki Interdisciplinary Journal, 2024)
Generation Z views social media as something that cannot be separated from everyday life. On the one hand, social media can help the younger generation in building relationships, exchanging ideas, and as a learning tool. However, on the other hand, social media is a threat to the younger generation, in terms of the length of use of social media which has an impact on the nervous system and also as a result of too much information received on social media. This research uses a systematic literature review which aims to determine the impact of social media on mental health from a neurological and psychological perspective. From the data taken, it shows that excessive use of social media can cause anxiety, symptoms of depression, decreased self-esteem, and disturbed sleep quality. Additionally, this review highlights that cyberbullying, social comparison and social isolation can exacerbate these negative impacts. The results of this review show that it is important for young people to be aware and wise about the imbalance between using social media and being responsible in using it.